Assessing long-term fiscal developments - a new approach - António Afonso; Luca Agnello; Davide Furceri; Ricardo M. Sousa (European Central Bank (ECB), 2009)
We use a new approach to assess long-term fiscal developments. By analyzing the time varying behaviour of the two components of government spending and revenue - responsiveness and persistence - we are able to infer about the sources of fiscal behaviour. Drawing on quarterly data we estimate recursively these components within a system of government revenue and spending equations using a Three-Stage Least Square method. In this way we track fiscal developments, i.e. possible fiscal deteriorations and/or improvements for eight European Union countries plus the US. Results suggest that positions have not significantly changed for Finland, France, Germany, Spain, the United Kingdom and the US, whilst they have improved for Belgium, Italy, and the Netherlands.
Keywords: E62; H50; 330; Fiscal Deterioration; Fiscal sustainability; Finanzpolitik; Öffentlicher Haushalt; Dezentralisierung; Öffentliche Ausgaben; Politischer Konjunkturzyklus; Panel; EU-Staaten